Optical Fiber Fabry–Pérot Interferometer Based on an Air Cavity for Gas Pressure Sensing - Ben Xu; Yaming Liu; Dongning Wang; Dagong Jia; Chao Jiang (IEEE Photonics Journal)
An optical fiber Fabry–Pérot interferometer (FPI) based on an air cavity with a microchannel is proposed and demonstrated for gas pressure measurement. The inner air cavity is fabricated by fusion splicing a single-mode fiber (SMF) with a microhole at the end facet to another section of SMF, then creating a microchannel to vertically cross the air cavity to allow gas to flow in. As the air cavity is cascaded to a short section of SMF, a three-beam interference pattern is produced, which shifts with the gas pressure variation in the inner air cavity due to the refractive index change of the gas. In order to compensate the temperature effect, the multiple-dip tracing technique and the Fourier band pass filtering (FBPF) method are used simultaneously for gas pressure and temperature measurement. It is also found that by using the FBPF method, the gas pressure sensitivity does not depend on the resonant peaks/dips selected in the filtered spectrum of the device. The proposed device has a robust tip structure, miniature size, and high sensitivity (∼4.028 nm/MPa) and is easy to fabricate, which makes it attractive for highly sensitive and precise gas pressure measurement.